Comparing Interpretations of the Rosenberg Self-Esteem Scale With 4-, 5-, and 101-Point Scales. (6th April 2020) - Colvin, Kimberly F.; Gorgun, Guher; Zhang, Sijun
The Rosenberg Self-Esteem Scale was administered with a 1–4, 1–5, or 0–100 scale to 819 participants, to compare score interpretations across the different versions. A rating scale utility analysis revealed that the categories in the 101-point scale were used inconsistently; based on the analysis, adjacent categories were collapsed resulting in a 7-point scale with almost identical psychometric properties as the original. The interpretations based on the 101-point scale could lead to misinterpretations when compared with the 4- and 5-point versions.